Effects of Belt and Road Initiative on Chinese Stock Volatilities Connectivity: An Empirical Study of 5 Listed Chinese Companies - Yixi Li (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Based on the development of the Belt and Road initiative and its impact on the Chinese economy. This paper studies the impact of the initiative on the stocks of five Chinese listed companies through vine copula models. The range of time period cover from 2009 to 2019, and it is divided into the pre-period and post-period based on 2013. The structure and degree of dependence between stocks before and after the Belt and Road initiative were compared, and their fluctuations were analyzed. The empirical results displayed the dependence structures of five stocks are symmetric and positive. The degree of dependence between companies increased in the Post-BRI period compared with in the pre-period, which implies the BRI strengthens the ties between related Chinese companies. Then, the results from time-varying C-vine copulas confirmed the robustness of the results of the static C-vine copulas and showed significant dynamic dependence characteristics among five stocks in both periods. According to the regime switching time varying model, we find that stock volatility is influenced by the belt and road initiative process as well as other major events. At last, we measure the VaR and ES. The results showed that the investment risk of stocks was significantly reduced after the release of the BRI.